Managing people in commercial kitchens : a contemporary approach - Giousmpasoglou, Charalampos (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Managing People in Commercial Kitchens: A Contemporary Approach uses original research to argue that senior managers (Head Chefs) should differentiate their people management practices in kitchen brigades from those used in the hospitality industry more generally (induction, socialisation and performance evaluation) due to the group's strong occupational identity and culture. The understanding of chefs' work from a management perspective is critical for successful hospitality operations but has been historically under-researched. Chapters provide a detailed account of Chefs' work in commercial kitchens from an HRM perspective. Using occupational identity and culture as a vehicle, this book explores the different aspects of managerial work in commercial kitchen settings: general management, leadership, education and training, skills and competencies, managing deviant behaviour, managing stress and managing diversity (focused on gender segregation). The final chapter looks at future perspectives on this unique working environment and the many challenges arising from the latest developments such as the COVID-19 pandemic. Providing both theoretical insights and practical applications with the use of case studies throughout, this will be of great interest to upper-level students and researchers in hospitality, as well as a useful reference for current managers in the field"--
Introduction -- The Commercial Kitchen's Structure and Organisation -- Occupational Culture and Identity -- People Management and Leadership in Commercial Kitchens -- Education and Training for Chefs -- Skills and Competencies for Chefs -- Gender and Diversity Issues in Commercial Kitchens -- Kitchen Deviance -- Banter, Bullying and Violence -- AOD Use and Coping with Stress -- Future Trends.
OCLC-licensed vendor bibliographic record.
Keywords: Food service -- Personnel management; Food service management; Food service employees; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism